The dilatation of main pulmonary artery and right ventricle observed by enhanced chest computed tomography predict poor outcome in inoperable chronic thromboembolic pulmonary hypertension. Issue 94 (September 2017) - Ema, Ryogo; Sugiura, Toshihiko; Kawata, Naoko; Tanabe, Nobuhiro; Kasai, Hajime; Nishimura, Rintaro; Jujo, Takayuki; Shigeta, Ayako; Sakao, Seiichiro; Tatsumi, Koichiro
Highlights: Dilatation of the pulmonary artery and right ventricle on chest CT are often observed in patients with pulmonary hypertension. The clinical significance of these image findings has not been defined in chronic thromboembolic pulmonary hypertension. Main PA/AA ratio was associated with the risk for clinical exacerbation and RV/LV raito was associated with the risk for poor prognosis in CTEPH. Abstract　: Background: Dilatation of the pulmonary artery and right ventricle on chest computed tomography images is often observed in patients with pulmonary hypertension. The clinical significance of these image findings has not been defined in chronic thromboembolic pulmonary hypertension. We investigated whether the pulmonary arterial and right ventricle dilatation was associated with poor outcome in chronic thromboembolic pulmonary hypertension. Methods: This was a retrospective cohort investigation in 60 subjects with inoperable chronic thromboembolic pulmonary hypertension diagnosed consecutively between 1997 and 2010 at Chiba University Hospital. Digital scout multi-detector chest computed tomography images were obtained. The main pulmonary arterial to ascending aortic diameter ratio and the right ventricular to left ventricular diameter ratio were calculated. Results: Main pulmonary arterial to ascending aortic diameter ratio ranged from 0.85 to 1.84, and right ventricular to left ventricular diameter ratio ranged from 0.71 to 2.88. During the observation period of 1284.5 days (range, 21–4550 days), 13 patients required hospitalization due to worsening; 6 of them died. Kaplan–Meier analysis showed significant differences in hospitalization between the patients with main pulmonary arterial to ascending aortic diameter ratio of ≥1.1 and <1.1 (log-rank test, p = 0.014) and between the patients with right ventricular to left ventricular diameter ratio of ≥1.2 and <1.2 (log-rank test, p = 0.013). There was a significant difference in the prognosis between the patients with RV/LV ratio ≥ 1.2 and those with RV/LV ratio < 1.2 (log-rank test, p = 0.033). Conclusions: Main pulmonary arterial to ascending aortic diameter ratio measured using enhanced CT images was associated with the risk for first clinical exacerbation, and right ventricular to left ventricular diameter ratio was associated with the risk for poor prognosis in inoperable chronic thromboembolic pulmonary hypertension.